MAIN DIRECTIONS OF IMPROVEMENT OF THE PROCESS OF INVESTMENT ATTRACTION - Baxriddin Jurayevich, Mahmudov; Mukhtasar Fazliddin qizi, Abdurakhmanova (IJBLE Scientific Publications Community Inc., 2020)
In this fast-changing world, conflicts of interest and rivalry between countries are growing. In such a difficult international environment, it is important to keep our country competitive in the region and in the world. Based on the “Strategy of actions on social and economic development of the Republic of Uzbekistan for 2017-2021” adopted for achievement of this goal, the priority directions of our development for the next years are clearly defined. In particular, 76 thousand projects totaling 21 trillion and 1 billion have been implemented within the framework of the state program